Analisis SWOT Potensi Pengembangan Candi Ramah Lingkungan Menuju SDGS - Suzana, Asih; Adriansyah, Endi; Dony, Wari; Qolbi, Muhammad Khofidul; Nalendra, Brama; Syaiful, M (Universitas Batanghari, 2025)
Muaro Jambi Temple as a national cultural heritage area, waste management in the area should implement a zoning system in accordance with PP No. 1 of 2022 in article 82. The temple tourism has great potential to be developed. This is supported by the location of Muaro Jambi Regency which is very strategic because it is close to a big city, namely Jambi City, resulting in high accessibility. The conditions at the temple tourist attraction actually have the potential for beauty and uniqueness that are very interesting, because the lack of transportation there causes a lack of interest in tourists to visit it. Development efforts to increase the attractiveness of tourists to temple tourist attractions need to be carried out. in this study is to determine the internal, external and combined potential of each tourist attraction and to determine the strategy for developing environmentally friendly tourist attractions to make superior tourist attractions based on their level of potential